Highly Uneven Distribution of Tenofovir-Selected Simian Immunodeficiency Virus in Different Anatomical Sites of Rhesus Macaques - Magierowska, Magdalena (American Society for Microbiology, 2004)
Antiviral tenofovir monotherapy was used to determine whether drug-selected simian immunodeficiency virus (SIV) variants replaced their wild-type progenitors at the same rate in different tissues of six rhesus macaques. The relative frequencies of drug-resistant and wild-type genotypes were measured longitudinally in blood and in 23 lymphoid and nonlymphoid tissues collected at necropsy. The mutant/wild-type genotype ratio was measured using a heteroduplex tracking assay targeting tenofovir-selected SIV reverse transcriptase codons. After the initiation of tenofovir treatment in animals with high steady-state viremia levels, resistant genotypes emerged in the plasma within 1 to 8 weeks and in five of six cases reached frequencies of nearly 100% within 4 to 25 weeks. The appearance of tenofovir-resistant genotypes in peripheral blood mononuclear cell (PBMC) DNA was generally delayed by 1 to 2 weeks and in one case was completely absent. Necropsies performed 8 to 55 weeks after the initiation of tenofovir treatment showed the frequency of resistant SIV genotypes to be generally higher in tissue RNA than DNA fractions. The frequency of drug-resistant genotypes varied widely between anatomical sites, including different lymph nodes of the same animal. Except for the epidydimis, the tissues with the lowest rates of proviral replacement by tenofovir-resistant genotypes differed between animals. The highly uneven distribution of tenofovir-resistant genotypes in different tissues seen shortly after the initiation of tenofovir monotherapy may reflect differences in local antiviral drug selection pressures and/or the stochastic effect of small effective populations of drug-resistant variants randomly seeding different anatomical sites early in therapy.